GRANDPARENTING OF KOREAN GRANDMOTHERS AND THEIR DEPRESSIVE SYMPTOMS: USING PROPENSITY SCORE MATCHING. (11th November 2018) - Lee, E; Jun, H
Abstract: Studies conducted on the relationships between grandparenting and grandparents' wellbeing have mainly reported the negative results of providing care for grandchildren. Most of them, however, were carried out targeting custodial grandparents taking the caregiving role in response to a parenting crisis of their adult children. Thus, the negative results of grandparenting found in previous research might have directly come from the caregiving situation, and studies targeting non-custodial grandparents found that raising grandchildren may actually have positive results. Therefore, this study aims to examine the effects of grandparenting on depression among Korean grandmothers who usually take the caregiving role to support their working adult children and have strong sense of family caregiving obligation. Data comes from the second wave of the Korean Longitudinal Study of Ageing and the study samples were grandmothers aged 47–85; 208 grandmothers who spent 10 or more hours a week taking care of their grandchildren under the age of 10 in the last year (caregiver), and 3, 248 grandmothers who did not take care of their grandchildren or who spent less than 10 hours a week (non-caregiver). In order to minimize selection bias and to examine causal effects more precisely, the propensity score matching method was used for the analysis. The results indicated that grandmothers raising grandchildren showed lower depression levels compared to their counterparts. These results suggest that grandmothers may experience better mental health by providing caregiving to their grandchildren and that the impacts of grandparenting could be different depending on cultural backgrounds and the caregiving situation.